Anisotropy Effects in the Shape‐Memory Performance of Polymer Foams. Issue 4 (16th April 2021) - Sauter, Tilman; Kratz, Karl; Madbouly, Samy; Klein, Frank; Heuchel, Matthias; Lendlein, Andreas
Abstract : Back Cover : In article number 2000730 by Andreas Lendlein and co‐workers, a temperature‐controlled micro‐bench vise is applied to program anisotropic PDLCL foams into a temporary shape and to observe their stress‐free recovery upon heating. Differences in the geometry of the pore deformationen along the two axes of the anisotropic system become apparent during deformations. Most pores recover to their original shapes with a considerable reduction in the pore size.